2014
DOI: 10.1158/0008-5472.can-13-0813
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Brain Tumor Cells in the Peripheral Blood by a Telomerase Promoter-Based Assay

Abstract: Blood tests to detect circulating tumor cells (CTC) offer great potential to monitor disease status, gauge prognosis, and guide treatment decisions for patients with cancer. For patients with brain tumors, such as aggressive glioblastoma multiforme, CTC assays are needed that do not rely on expression of cancer cell surface biomarkers like epithelial cell adhesion molecules that brain tumors tend to lack. Here, we describe a strategy to detect CTC based on telomerase activity, which is elevated in nearly all t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 25 publications
6
162
1
4
Order By: Relevance
“…[27] Recent studies reported that the number of circulating tumor cells in the blood of glioma patients is approximately 10 cells ml –1 . [28,29]. These suggest that there is a possibility that the IDH1 status can be determined with our device using cerebrospinal fluid and blood.…”
Section: Discussionmentioning
confidence: 94%
“…[27] Recent studies reported that the number of circulating tumor cells in the blood of glioma patients is approximately 10 cells ml –1 . [28,29]. These suggest that there is a possibility that the IDH1 status can be determined with our device using cerebrospinal fluid and blood.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the identification of glioma-derived CTCs in the circulation of such patients posttreatment (after chemoradiation therapy) is prognostic, with a reduction in CTCs indicating treatment response and an increase in CTCs indicating disease progression (44,45). …”
Section: Discussionmentioning
confidence: 99%
“…This might lead to suboptimal induction of immune response to tumors located in the brain as compared to other sites. Nonetheless, it cannot be entirely excluded that immune responses to brain tumors are elicited in the periphery in response to circulating tumor cells reaching secondary lymphoid organs; these having been reported in a significant number of patients with GBM (82, 83). …”
Section: Immune Responses To Tumors Arising In the Brainmentioning
confidence: 99%